Hubungan Faktor Psikologis Ibu Dengan Kejadian Balita Stunting Di Wilayah Kerja Puskesmas Merakurak Tuban - Utami, Emy Nur; Sumiatin, Titik; Su’udi, Su’udi; P, Teresia Retna (Peneliti.net, 2024)
Stunting is a global problem because of its high prevalence. According to several studies, one of the factors that causes a high prevalence of stunting is the psychological factor of the mother. Mother's psychology can directly or indirectly affect the child's parenting pattern, because it can cause a decrease in the mother's sensitivity in carrying out her role in the family, especially in sensitivity to toddler nutrition. The purpose of this study was to determine the psychological factors of the mother that were most dominant in the incidence of stunting under five. The design of this study uses a correlation cross-sectional approach. The population in this study were mothers who had toddlers in the working area of ​​the Merakurak Health Center as many as 109 mothers. The sampling technique used is simple random sampling. The instrument in this study was a questionnaire. Data analysis using chi-square and logistic regression. Based on the results of statistical tests, there are no psychological factors that most dominantly affect mothers with stunting toddlers, with the results of mothers experiencing anxiety, namely 82.6%, stress 56.2%, lack of social support 45%, emotional 89.9%, and depression 25.7%. However, based on this study, it was found that the most common psychological problem experienced by mothers with stunting toddlers was anxiety Mothers who experience anxiety can have an impact on providing nutrition to toddlers, one of which can cause stunting toddlers, because mothers are more likely to be anxious in dealing with situations providing nutrition to toddlers